Analysis of Abnormal Returns and Financial Performance during Pandemic COVID-19: Jakarta Islamic index (JII) - Ashari, Maharani Syamsyyah; Geraldina, Ira; Simorangkir, Panubut (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
This research uses quantitative research methods to determine the significant difference in the effect of financial performance on abnormal returns before and during the COVID-19 pandemic. Companies that are categorized as the Jakarta Islamic Index (JII) for 2020 are used as research samples with a saturated sampling technique, so the sample used in this research is 30 JII companies. Multiple linear regression analysis was used in testing the hypothesis with the E-Views version 10 program and a significance level of 5% (0.05). The test results show 1) the current ratio does not have a significant effect on abnormal returns, 2) profit margin does not have a significant effect on abnormal returns, 3) the debt to equity ratio does not have a significant effect on abnormal returns, 4) day sales outstanding does not. has a significant effect on abnormal returns. The results of descriptive statistics in the research show that there is no significant difference between the current ratio, profit margin, debt to equity, and outstanding day sales both before the COVID-19 pandemic and during the Covid-19 pandemic in Indonesia.